2012
DOI: 10.3945/jn.111.147447
|View full text |Cite
|
Sign up to set email alerts
|

A Dietary Pattern Including Nopal, Chia Seed, Soy Protein, and Oat Reduces Serum Triglycerides and Glucose Intolerance in Patients with Metabolic Syndrome

Abstract: Metabolic syndrome (MetS) is a health problem throughout the world and is associated with cardiovascular disease and diabetes. Thus, the purpose of the present work was to evaluate the effects of a dietary pattern (DP; soy protein, nopal, chia seed, and oat) on the biochemical variables of MetS, the AUC for glucose and insulin, glucose intolerance (GI), the relationship of the presence of certain polymorphisms related to MetS, and the response to the DP. In this randomized trial, the participants consumed thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
79
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 48 publications
2
79
1
6
Order By: Relevance
“…A correlation between high-saturated fatty acids (SFA) and low polyunsaturated fatty acid (PUFA) intake and diseases such as cardiovascular diseases, diabetes, and metabolic syndrome were widely reported [10]. Besides, the additive effect of α-linolenic acid (ALA) and n-3 long-chain PUFA was observed to exhibit cardio-protective effects in women [11], which led to consequent human clinical studies of chia on disease risk factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A correlation between high-saturated fatty acids (SFA) and low polyunsaturated fatty acid (PUFA) intake and diseases such as cardiovascular diseases, diabetes, and metabolic syndrome were widely reported [10]. Besides, the additive effect of α-linolenic acid (ALA) and n-3 long-chain PUFA was observed to exhibit cardio-protective effects in women [11], which led to consequent human clinical studies of chia on disease risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…This difference could be due to the treatment durations employed and also the actual biochemical components of the dietary chia seed used in the various studies. Nevertheless, later studies [10] demonstrated the benefits of chia to human health. Today, chia is still an essential element in the diet of the inhabitants of Mexico and several Central American countries, becomes an increasingly popular food and is common in supermarkets and health food stores around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Este resultado puede explicarse en parte por el tipo de alimentos que conforman este patrón (específicamente las leguminosas y tortilla de maíz), y el efecto que éstos ejercen sobre el metabolismo de la glucosa y los lípidos, al disminuir su absorción intestinal. 7,35,36 La tendencia a una menor posibilidad de desarrollar hiperglucemia, baja concentración de HDLc, hipertensión y SM, que confiere el consumo del patrón 1 en este estudio, concuerda con los resultados descritos por Esmaillzadeh y colaboradores en mujeres adultas iraníes, donde el patrón dietético "saludable" (rico en frutas, pollo, leguminosas, crucíferas y verduras de hoja verde y granos enteros) fue asociado con menor posibilidad de SM y resistencia a la insulina, mientras que la ingesta elevada del patrón dietético "occidental" se asoció positivamente. 12 Por otro lado, la asociación negativa entre el patrón 2 y la posibilidad de tener baja concentración de HDLc puede deberse a un mayor consumo de oleaginosas, las cuáles, se sabe, tienen un efecto benéfico sobre los lípidos séricos.…”
Section: Discussionunclassified
“…Guevera-Cruz et al [31] przeprowadzili randomizowane badanie wśród osób z zespołem metabolicznym. Jedna z grup miała za zadanie utrzymanie diety zredukowanej o 500 kcal.…”
unclassified
“…W obu grupach zauważono zmniejszenie masy ciała i obwodu talii, a w grupie osób spożywających koktajl zauważono zmniejszenie stę-żenia trójglicerydów i białka CRP oraz poprawę tolerancji glukozy. Efekt metaboliczny może być również przypisywany innym składnikom koktajlu, ale warto wziąć pod uwagę obecność nasion chia jako składnika [31].…”
unclassified